Dendrite-free lithium–metal batteries at high rate realized using a composite solid electrolyte with an ester–PO4 complex and stable interphase. Issue 40 (7th October 2019) - Zhang, Zhaoshuai; Zhang, Long; Liu, Yanyan; Yang, Tingting; Wang, Zhiwen; Yan, Xinlin; Yu, Chuang
Abstract : PO4 3− –ester interactions realize dendrite-free Li deposition in PCL–LAGP, evidenced by galvanostatic cycling and in situ TEM observations. The corresponding battery achieves high coulombic efficiency ∼100% and a rate capability ≥10C. Abstract : Uneven growth of lithium dendrites and large volume expansion of Li–metal batteries based on a Li anode upon cycling cause low coulombic efficiency, fast capacity decay, and safety concerns. Herein, inspired by the hybrid concept we for the first time prepare a PCL–LAGP composite polymer electrolyte. The chemical interactions of PO4 3− and ester groups are revealed through a detailed investigation. Given the synergistic effect of organic–inorganic hybrids, the composite electrolyte achieves dendrite-free Li deposition, which is confirmed by long-term galvanostatic polarization tests over 4 mA cm −2 and in situ TEM observation of potentiostatic cycling. Moreover, the soft feature of PCL results in the formation of a stable interphase layer with low resistance to sustain the volume expansion. A LiFePO4 /Li all-solid-state battery demonstrates a high coulombic efficiency close to 100%, superior cycling stability and a rate capability of over 10C. The PCL–LAGP composite is a promising solid electrolyte for practical applications at high current density.